Journalism of Paper Newspapers in Light of the Competition of the Electronic Press / (A Field Study of Yemeni Daily Newspapers) - الدناني عبد الملك (ALBAHITH ALALAMI, 2016)
The researcher seeks to get scientific facts through knowing the relationship between the priorities of Yemeni audience in follow-up paper daily newspapers compared to surfing publics the online journalism sites and the nature of information obtained from online journalism sites and printed paper newspapers and the impact of the daily newspapers in the priority of issues and political events among a sample of a group of Yemeni readers in order to identify the extent to keep up the paper daily newspapers of the development in the field of online journalism and the extent of reading paper newspapers under the intense competition by online journalism sites, and are paper newspapers able to keep pace with the actual developments provided by modern technologies in the field of media and information and their various uses through the reality of Yemeni paper newspapers among means of communication to understand and comprehend the recent developments in the field of electronic newspapers.